Implementing Collaborative Writing to Teach Writing for Non-English Major Students - Zahrotun Hanifah; Suparno; Slamet Supriyadi (International Journal of Language Teaching and Education, 2019)
This study aims to expose and explore the implementation of collaborative writing in a non-English department in a state university in Surakarta, Indonesia. The method used in this study was descriptive qualitative focusing on the procedures of collaborative writing. The participants of the study were 63 students who were then divided into 16 groups for their collaborative project. In collecting the data, the researcher conducted document analysis, observations, and interview with both the lecturer and students. Three students were selected purposively for interview. The findings of this study were specific procedures of collaborative writing for non-English major students and different types of collaborative writing strategy applied by students. The procedures of collaborative writing for non-English major students comprised forming group, determining topic, outlining, drafting, editing and revising, and submitting. Meanwhile, the strategies applied by students in collaborative writing were reactive writing and parallel writing. In the implementation of collaborative writing, students also faced some difficulties. Those are in terms of cooperation between group members, irresponsible group members, and active learning. In implementing collaborative writing especially for non-English major students, it is better for teachers to consider the language proficiency of the students. In addition, teachers’ guidance is very important in the process of collaborative writing for non-English major students.